An efficient EYDFA with a 54 dB small signal gain - Muhd-Yassin, S. Z.; Harun, Sulaiman Wadi; Abdul Rashid, Hairul Azhar; Abd-Rahman, M. K.; Abd Rahman, Faidz; Ahmad, Harith (Wiley Periodicals, 2007)
An efficient erbium/ytterbuam codoped fiber amplifier is demonstrated by using a dual-stage cofiguration with a midway optical isolator and a band-pass filter (BPF). The amplifier achieved a maximum low signal gain of 54 dB and a corresponding noise figure of 6.5 dB(1536 mn) using the input signal power and total pump power of -50 dBm and 140 mW. respectively. The gain obtained by the amplifier was about 12.5 dB higher than the gain of conventional single-stage amplifier whereas its noise figure improvements by blocking backward and forward propagating amplified spontaneous emission. (c) 2007 Wiley Periodicals.